Ultramafic pseudotachylytes in high-pressure metamorphogenic peridotite from Luobusha, Tibet: a record of crustal paleo-earthquakes - Zhang, Haoran; Xu, Xiwei; Yang, Saihong (Frontiers in Earth Science, 2023)
In this paper, we report an occurrence of ultramafic pseudotachylytes, providing fault-rock evidence of paleo-earthquakes, from the Luobusha ophiolite complex in the Yarlung Zangbo suture zone. The pseudotachylytes form hairline-thin aphanitic veinlets and vein networks bounded by micro-damage zones cutting through the host harzburgite, forming flow banding in some places. The pseudotachylyte veins are dominated by close-knit ultrafine-grained minerals consisting of olivine, orthopyroxene, serpentine, spinel, and magnetite, cemented by an extremely fine matrix. As the primary component of the pseudotachylyte veins, olivine occurs as microphenocryst showing zoning from core to rim and as irregularly shaped microlite immersed in the interstitial material. Zoned crystals of olivine developed with Mg-rich cores and more Fe-rich rims. Microlite diagnosis of crystallization in a quenched melt includes dendritic, skeletal, and poikilitic olivine crystals, which are typical of ultramafic pseudotachylyte. The olivine microlites contain higher amounts of Ca, Al, and Cr but a lower Ni content compared with the host harzburgite olivine. Irregularly shaped chrome-spinel crystals are chemically zoned as well, indicating an Fe-rich rim overgrowth. Ni sulfide droplets interspersing among the matrix imply melt occurrence. The presence of a micro-fibrous and micro-vesicular interstitial matrix also indicates a melting-related origin. Ultracataclastite veins associated with pseudotachylyte transecting serpentine are observed, which convey that heat was generated during rapid comminution and injection. The characteristic petrography, microtextures, and chemical inhomogeneities meet the criteria of ultramafic pseudotachylyte and reveal a mixed genesis via a combination of crushing and melting. The development of extremely tiny globular prograde serpentine inclusions (∼100 nm) in the olivine microlites is ascribed to the dehydration reaction of serpentine to olivine within the pseudotachylyte. The Luobusha metamorphogenic peridotite was subjected to serpentinization after having emplaced in the crust and subsequently to high-pressure metamorphism. The pseudotachylytes were generated in the crust after the high-pressure metamorphism and did not descend to a greater depth. Flash ultra-comminution associated with frictional heating may release fluids via localized heat-driven prograde reactions in the crust.